IFSB Role in Preventing Financial Crises and Islamic Ethics Perspective - Adi Rahmannur Ibnu (Ijtimā`iyya: Journal of Muslim Society Research, 2018)
Islamic Financial Services Board (IFSB) acts as the international regulatory and supervision framework for Islamic financial services institution. Though Islamic financial industries keep growing in promising pace, they still experience some criticisms; one of them is an underestimate claim regarding Islamic finance soundness and safety which notoriously promoted to be better than the non-Islamic is lack of evidence. This claim, however, serves as the early warning to the trajectory of Islamic finance development and global vision which seems to employ. Thus, this study addresses this challenge by analyzing IFSB’s published frameworks based on the Islamic ethics. This is a descriptive inquiry which employed library-study approach. The result of this study suggests that IFSB should be more focus on human adversaries since moral hazard, either done collectively or individually, plays determining role in some systemic financial crises in the last two decades. The suggested action plan is discussed in the conclusion section.